2018
DOI: 10.11113/jt.v80.12293
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Benzohydroxamic Acid Metal Complexes and Their Cytotoxicity Study

Abstract: Hydroxamic acids (RCONHOH) are versatile compounds that constitute a significant biological importance. The syntheses, physico-chemical and characterization of benzohydroxamic acid (BHA) and its metal complexes (VO(IV), Cr(III) and Ni(II)) are reported herein. The metal complexes were synthesized via condensation reaction of BHA and metal salts in 2:1 molar ratio using ethanol as reaction medium. The compounds were characterized by elemental analysis, spectral (infrared, UV-Vis, 1H and 13C NMR,), TGA, magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Literature contains numerous reports on the transport of the pharmacologically active vanadium(IV) and (V) complexes as well as the role of the ligand in various redox and uptake processes, wherein the active species formed depend upon the thermodynamic stability of vanadium complexes and the potential of ligand to cross the cell membrane in bodily fluids at physiological pH. 5769 The oxidovanadium(IV) hydroxamates 43,4547,70,71 have drawn considerable attention owing to their interesting biological activity over the last few years. In pursuit of new vanadium-based antimicrobials, the antimicrobial activity of the complexes 1 and 2 has been assayed.…”
Section: Resultsmentioning
confidence: 99%
“…Literature contains numerous reports on the transport of the pharmacologically active vanadium(IV) and (V) complexes as well as the role of the ligand in various redox and uptake processes, wherein the active species formed depend upon the thermodynamic stability of vanadium complexes and the potential of ligand to cross the cell membrane in bodily fluids at physiological pH. 5769 The oxidovanadium(IV) hydroxamates 43,4547,70,71 have drawn considerable attention owing to their interesting biological activity over the last few years. In pursuit of new vanadium-based antimicrobials, the antimicrobial activity of the complexes 1 and 2 has been assayed.…”
Section: Resultsmentioning
confidence: 99%
“…A significant shift in υ(C=O) vibration to lower and υ(C-N) vibration to higher wave number may be ascribed to electron transfer to υ(V=O) mode. Appearance of new band at 484 cm -1 may be assigned to υ(M-O) bond [58].…”
Section: Vibrational Spectroscopymentioning
confidence: 97%
“…However, the authors found it difficult to find any publications reporting a close absorption wavelength for the molecular form of BHA. The reported wavelengths were 220 nm (Hassan et al, 2019), 224 nm (Hassan et al, 2018), and 227 nm (Elizondo-Álvarez et al, 2021, Fang et al, 2018, Glorius et al, 2007. It has been suggested however that the peak corresponded to the neutral form of BHA appears at 228 nm at low acidities, at 236 nm at intermediate acidities, and at high acidities at the region of 240-250 nm in sulfuric, hydrochloric and perchloric acid solutions (Ghosh, 2003).…”
Section: Xps Analysismentioning
confidence: 99%